Collateral Values by Asset Class: Evidence from Primary Securities Dealers - Bartolini, Leonardo; Hilton, Spence; Sundaresan, Suresh; Tonetti, Christopher (Review of Financial Studies, 2011)
Using data on repurchase agreements by primary securities dealers, we show that three classes of securities (Treasury securities, securities issued by government-sponsored agencies, and mortgage-backed securities) can be formally ranked in terms of their collateral values in the general collateral (GC) market. We then show that GC repurchase agreement (repo) spreads across asset classes display jumps and significant temporal variation, especially at times of predictable liquidity needs, consistent with the "safe haven" properties of Treasury securities: These jumps are driven almost entirely by the behavior of the GC repo rates of Treasury securities. Estimating the "collateral rents" earned by owners of these securities, we find such rents to be sizable for Treasury securities and nearly zero for agency and mortgage-backed securities. Finally, we link collateral values to asset prices in a simple no-arbitrage framework and show that variations in collateral values explain a significant fraction of changes in short-term yield spreads but not those of longer-term spreads. Our results point to securities' role as collateral as a promising direction of research to improve understanding of the pricing of money market securities and their spreads. The Author 2010. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.